Design-specific mechanistic regulation of the sensing phenomena of two Schiff bases towards Al3+. Issue 60 (8th June 2016) - Shweta; Neeraj; Asthana, Sharad Kumar; Mishra, Rakesh K.; Upadhyay, K. K.
Abstract : We report herein two optical probes (R1 andR2 ) for the fluorogenic detection of Al 3+ at the level of 10 −8 M. Abstract : We report herein two optical probes (R1 andR2 ) for the fluorogenic detection of Al 3+ at the level of 10 −8 M.R1 andR2 were synthesized by simple Schiff base condensation of 4-amino-3-hydroxy-1-naphthalene sulfonic acid with 5-bromosalicaldehyde and 2-hydroxy-1-naphthaldehyde, respectively. The same were characterized by various spectroscopic techniques.R1 andR2 both underwent fluorescence emission upon their respective interactions with Al 3+ in an ethanol : water mixture (4 : 1, v/v). The binding modes of the receptors with Al 3+ were studied through 1 H NMR spectroscopy, Job plots, and HR-MS, as well as through binding constant determination involving fluorescence titration data. The quenching of –CN isomerization and of photoinduced electron transfer (PET) seem to be responsible for the fluorogenic switch-on situation ofR1 andR2 with Al 3+ . At the same time, excited state intramolecular proton transfer (ESIPT) also plays an important role in the ratiometric fluorescence response ofR2, which is a consequence of a minor structural variation inR1 where the bromophenyl moiety is replaced with a naphthalene moiety. The mechanistic aspects of the sensing phenomenon are discussed in terms of 1 H NMR titration as well as theoretical calculations at the density functional level.